Political Economy of the Budget in the Parliament: An Analysis of the Pattern of Changes in the Budget Bill in Iranian Parliament - Mostafa Dinmohammadi; Sajedeh Bakhshi Balani (فصلنامه پژوهش‌های اقتصادی ایران, 2021)
The purpose of this study is to identify the pattern of quantitative changes in budget bills in the Iranian parliament. Analyzing the Iranian parliament's role in budgeting shows that 30 percent of the general budget increases have occurred in the parliament in the 24 past years. The parliament has played a stabilizing role and increasing public expenditures. Political alignment periods have not made a significant difference in budget changes in parliament. In the political change years (the last year of the government and the first year of the parliament), the total growth of the general budget expenditures of the bill has been significantly higher than the other years. Organizations outside the executive branch have more bargaining and rent-seeking power. They have the largest budget increases in the parliament by a share of 76 percent. The study shows that the parliament in Iran has unlimited powers in amending the budget bills. This conclusion is without considering the qualitative changes in the notes of the single article of the budget؛ if these qualitative changes are also considered, the role of the parliament will increase in the budget changes.